Synthesis, characterization and adsorptive performance of MgFe2O4 nanospheres for SO2 removal - Zhao, L.; Li, X.; Zhao, Q.; Qu, Z.; Yuan, D.; Liu, Shaomin; Hu, X.; Chen, G. (Elsevier BV, 2010)
A type of uniform Mg ferrite nanospheres with excellent SO2 adsorption capacity could be selectively synthesized via a facile solvothermal method. The size of the MgFe2O4 nanospheres was controlled to be 300–400 nm in diameter. The structural, textural, and surface properties of the adsorbent have been fully characterized by a variety of techniques (Brunauer–Emmett–Teller, BET; X-ray diffraction analysis, XRD; scanning electron microscopy, SEM; and energy-dispersive X-ray spectroscopy, EDS). The valence states and the surface chemical compositions of MgFe2O4 nanospheres were further identified by X-ray photoelectron spectroscopy (XPS). The behaviors of SO2 oxidative adsorption on MgFe2O4 nanospheres were studied using Fourier transform infrared spectroscopy (FTIR). Both the sulfite and sulfate species could be formed on the surface of MgFe2O4. The adsorption equilibrium isotherm of SO2 was analyzed using a volumetric method at 298 K and 473 K. The results indicate that MgFe2O4 nanospheres possess a good potential as the solid-state SO2 adsorbent for applications in hot fuel gas desulfurization.